Efficacy and safety of 5% imiquimod cream compared to 10% KOH solution for elimination of molluscum contagiosum lesions in adults - Bianti, Marsha; Rheza, Agung Muhammad; Marina, Arinda; Hilma, Rizka Farah; Mahri, Sarah; Nuary, Teffy; Rihatmadja, Rahadi (UI Scholars Hub, 2019)
Background: Molluscum contagiosum (MC) is a benign infection caused by the Molluscipox virus that most often affects children and sexually active adolescents. Various topical therapeutic options are available, however, no single intervention is convincingly effective. Potassium hydroxide (KOH) solution is widely used but its usefulness is hampered with adverse effects. Newer preparation, 5% imiquimod cream seems to be as, if not more, effective. However, it is not legally available yet in Indonesia. Aim: To assess the efficacy and safety of 5% imiquimod cream in treating adult molluscum contagiosum. Methods: Literature search was done through Pubmed, EBSCO, dan Cochrane databases. Inclusion criteria included articles in English, available in free full text and matched with the clinical question as well as providing the clinical outcome of papules clearance within 12 weeks. Results: There were three articles found to be related to the clinical question and they were critically appraised for their validity, importance, and applicability. Conclusion: Only two studies were valid and further assessed for their importance and applicability. In regards to importance, imiquimod has fewer side effects than KOH, yet it was not constantly shown to be superior to KOH in curing MC lesions. We conclude that KOH solution is the preferred treatment of MC in adults.